Numerical Approach for Solving Two-Dimensional Time-Fractional Fisher Equation via HABC-N Method - Liu, Ren; Wu, Lifei (Communications on Applied Mathematics and Computation (Online), 2025)
For the two-dimensional time-fractional Fisher equation (2D-TFFE), a hybrid alternating band Crank-Nicolson (HABC-N) method based on the parallel finite difference technique is proposed. The explicit difference method, implicit difference method, and C-N difference method are used simultaneously with the alternating band technique to create the HABC-N method. The existence of the solution and unconditional stability for the HABC-N method, as well as its uniqueness, are demonstrated by theoretical study. The HABC-N method’s convergence order is O τ 2 - α + h 1 2 + h 2 2 . The theoretical study is bolstered by numerical experiments, which establish that the 2D-TFFE can be solved using the HABC-N method.